Studying Identities with Experiments: Weighing the Risk of Posttreatment Bias Against Priming Effects - Klar, Samara; Leeper, Thomas; Robison, Joshua (Journal of experimental political science, 2020)
Scholars from across the social sciences argue that identities – such as race, ethnicity, and gender – are highly influential over individuals’ attitudes, actions, and evaluations. Experiments are becoming particularly integral for allowing identity scholars to explain how these social attachments shape our political behavior. In this letter, we draw attention to how identity scholars should approach the common practice of assessing moderators, measuring control variables, and detecting effect heterogeneity using covariates. Special care must be taken when deciding where to place measures of demographic covariates in identity-related experiments, as these cases pose unique challenges from how scholars traditionally approach experimental design. We argue in this letter that identity scholars, particularly those whose subjects identify as women or minorities, are often right to measure covariates of interest posttreatment.